Menggali Potensi Siswa dengan Mengadakan Kegiatan Perlombaan yang Bersifat Umum, di SMP Pasundan Leles - Sepih Septiyani B; Alvi Yusri I; Jasmine Orien A; Rica Handayati; Ikbal Maulana S; Samsul Samsul; Haura May I; Salmi Hazmi; Miftah Rezki F; Ahmad Mustofa A; Diana Farid (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to explore the potential of students at SMP Pasundan Leles through the implementation of general competitions. These competitions include various fields such as academics, arts, and sports, designed to develop students' talents and interests. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that these competitions can increase students' motivation to learn, hone their skills in various areas, and strengthen their self-confidence and cooperation among peers. Additionally, the activities provide students with opportunities to showcase their talents and potential, which may not be visible in daily classroom activities. Therefore, the competitions are expected to be an effective strategy in supporting the development of students' potential in the school environment.